El manejo de programas editores de partituras en el aprendizaje musical de los estudiantes del 6to semestre nivel técnico del conservatorio de música ¨Salvador Bustamante Celi¨. Período febrero-julio 2013 - Lituma Quezada, Julio Adrian (2015)
This research aims to inform ADVOCACY PROGRAM MANAGEMENT PUBLISHERS IN LEARNING MUSICAL SCORES OF 6TH SEMESTER STUDENTS OF TECHNICAL LEVEL CONSERVATORY OF MUSIC "SALVADOR BUSTAMANTE CELI". PERIOD FEBRUARY-JULY 2013. It has been structured and developed in accordance with the regulations in force graduation from the National University of Loja.Overall objective was formulated: Contributing to the musical education of 6th semester students technical level of the Music Conservatory "Salvador Bustamante Celi", through the implementation of programs of music publishers. The methods used for data collection and analysis were: scientific method, analytic - synthetic, descriptive, inductive - deductive, statistical, which allowed them to describe and explain the implementation of programs of music publishers in musical learning.The research instrument applied to both teachers and students of the 6th semester technical level of the Music Conservatory "Salvador Bustamante Celi" was a survey that was used to learn about the knowledge and implementation of programs of music publishers in student learning this level. It reached the following conclusions: program management score editors contributes to the formation of music students because it provides them with educational tools to make learning more agile and efficient, as corroborated by 100% of teachers surveyed and 97 % students. For programs score editors are useful, students must know their management and their chances very well. There is an average rate corresponding to 56% of students who manage and use software publishers and others do not by ignorance of this makes them appropriate to emphasize the need for learning to implement these programs and include them within musical training students.